2005
DOI: 10.1016/j.cub.2005.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Mad2 to the Kinetochore Requires the Rod/Zw10 Complex

Abstract: Compromising the activity of the spindle checkpoint permits mitotic exit in the presence of unattached kinetochores and, consequently, greatly increases the rate of aneuploidy in the daughter cells. The metazoan checkpoint mechanism is more complex than in yeast in that it requires additional proteins and activities besides the classical Mads and Bubs. Among these are Rod, Zw10, and Zwilch, components of a 700 Kdal complex (Rod/Zw10) that is required for recruitment of dynein/dynactin to kinetochores but whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
212
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(221 citation statements)
references
References 40 publications
8
212
1
Order By: Relevance
“…Larval neuroblasts were prepared and imaged as described previously (Buffin et al, 2005), using an Olympus IX-70 inverted microscope equipped with a focused xenon lamp and an OrcaER camera (Hammamatsu, Bridgewater, NJ), piloted by Cell-R hardware and software system (Olympus). Depending on the fly line, image acquisition times were 100 -400 ms for GFP and 250 -400 ms for red fluorescent protein (RFP).…”
Section: Larval Neuroblast Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Larval neuroblasts were prepared and imaged as described previously (Buffin et al, 2005), using an Olympus IX-70 inverted microscope equipped with a focused xenon lamp and an OrcaER camera (Hammamatsu, Bridgewater, NJ), piloted by Cell-R hardware and software system (Olympus). Depending on the fly line, image acquisition times were 100 -400 ms for GFP and 250 -400 ms for red fluorescent protein (RFP).…”
Section: Larval Neuroblast Imagingmentioning
confidence: 99%
“…In Drosophila neuroblasts, Mad2 is primarily in the nucleoplasm, but a fraction of it is associated with the NE (Buffin et al, 2005). To further explore Mad2's association with the NE, we directly compared the behavior of GFP-Mad2 with that of mRFP-Nup107 during mitotic entry and exit.…”
Section: The Association Of Mad2 With Npcs At the End Of Mitosis Is Amentioning
confidence: 99%
“…The formation of Bub3:BubR1:Cdc20 is accelerated in the presence of unattached chromosomes (Kulukian et al, 2009a) and it may be that MCC forms as an intermediate complex from which OMad2 rapidly dissociates (Kulukian et al, 2009a;Malureanu et al, 2009;Medema, 2009). Microtubule attachment depletes the template-complexes from the respective kinetochore, thereby silencing SAC-signaling locally (Buffin et al, 2005;Sivaram et al, 2009). Thus, after proper attachment of the last chromosome, SAC signaling ceases and passage to anaphase is granted.…”
Section: Formationmentioning
confidence: 99%
“…In another study, Savoian and colleagues used zw10 and rod Drosophila mutant spermatocytes to specifically perturb dynein localization at kinetochores [99,100] and showed that anaphase chromosome motion to the poles was severely affected in those mutants. However, some potential caveats with this experimental approach are related with the fact that zw10/rod are also required to recruit the SAC protein Mad2 to unattached kinetochores, thereby compromising SAC function [101][102][103]. Kinetochore dynein is also involved in the initial MT capture at the entry of mitosis, which could indirectly compromise chromosome motility if anaphase is triggered with normal kinetics [100].…”
Section: Kinetochore Dyneinmentioning
confidence: 99%